Dzielnica, ale jaka? Kilka uwag o epitetach określających getto warszawskie - Witkowska-Krych, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The text is an attempt of presenting and analyzing the linguistic landscape connected with describing and/or precising the features of the Warsaw Ghetto, i.e. Jewish closed residential area in Warsaw, created by the Germans in 1940 for more than four hundred thousand Jews. The most frequent phrase that was replacing the word „ghetto” was the formulation „Jewish residential district”, which was the direct translation of the German term „Jüdischer Wohnbezirk”, officially used to name this particular area. A collection of epithets that accompany the word „district”, found in the historical sources, both of Jewish and Polish origin, written during the war or many years after the war had ended, coming from various sematic fields, show the attitude of the speaker or writer to this new topographic solution, that not only divided the city, but also stigmatized and separated physically its inhabitants.
What kind of a District? A few Remarks about the Epithets describing the Warsaw Ghetto
Keywords: Warsaw Ghetto; Jews; epiteths; naming; describing; Jewish residential area; getto warszawskie; Żydzi; epitety; nazywanie; określanie; żydowska dzielnica mieszkaniowa